Pengaruh Independensi dan Kompetensi Auditor Internal Pada Kualitas Audit di LPD Kota Denpasar - Kadek Ayu Radananda Sukmadewi; I Ketut Yadnyana (UNHI Press, 2024)
This research aims to obtain empirical evidence regarding the influence of the independence and competence of internal auditors on audit quality in LPD Denpasar City. The sample selection technique in this research is non-probability sampling with a saturated sampling type. The total population and sample for this study were 35 LPDs with 105 respondents, but there was one incomplete questionnaire so the respondents used were 104 respondents. This research uses multiple linear regression analysis techniques with the help of the SPSS (Statistical Package for the Social Sciences) program. The results of this research indicate that the independence and competence of internal auditors have a positive effect on audit quality in LPD Denpasar City. The theoretical implication of this research is that it has confirmed that the theory of planned behavior (TPB) and attribution theory can empirically prove that independence and competence have a positive influence on audit quality in LPD Denpasar City. The practical implication of this research is to provide material for consideration and motivation to internal auditors, especially the Supervisory Body (Panureksa), in carrying out their audit duties more seriously, with honesty, independence and competence.